Ulcer recurrence after in‐hospital treatment for recalcitrant venous leg ulceration. (25th April 2013) - Reeder, S.; de Roos, K.‐P.; de Maeseneer, M.; Sommer, A.; Neumann, H.A.M.
Summary Background Leg ulceration caused by chronic venous disease occurs in 1% of the adult Western population. A majority of these patients is successfully treated in the outpatient setting. A minority of patients is hospitalized, most frequently because of the lack of healing tendency. The literature provides recurrence rates for ulcer disease, but lacks specific data on recurrence rates after in‐hospital treatment of recalcitrant venous leg ulcers. Objectives To investigate time to ulcer recurrence after in‐hospital treatment of venous leg ulceration. Methods A multicentre, retrospective cohort study of patients admitted for leg ulceration between 1996 and 2007 was conducted. Results Data could be collected for 107 of the patients. Of these, 27 had conservative treatment (bed rest, local wound care, pain management) and 48 patients underwent surgical ulcer treatment with (n = 19) or without (n = 29) initial vacuum‐assisted closure (VAC) treatment. The treatment method was 'miscellaneous' in the remaining 32 patients. Median admission time was 30 days, median percentage of closure at discharge was 95%, and median time to ulcer recurrence 60 days. The Mann–Whitney U‐test showed significant differences between the conservative group and the surgery group, the latter having a longer length of hospital stay (P < 0·0001) and a higher percentage of ulcer closure (P < 0·0001), but there was no difference in time to ulcer recurrence (P = 0·273). Comparable differences were demonstrated between the conservative group and the VAC plus surgery group. No significant differences could be demonstrated between the surgically treated patients and those treated by VAC and surgery. Conclusions Hospital stay is significantly shorter in cases of surgical treatment of recalcitrant venous leg ulcers. Most ulcers recur within 2 months after hospital discharge. Recurrence of venous leg ulcers after hospital admission is independent of the method of treatment and cause of ulceration.